Research of Cocoa Fat Subtitution with Palm Fatty Oil in Chocolate Bar Making (Balai Riset dan Standardisasi Industri Pontianak, 2012)
So far, most of West Kalimantan cocoa beans sold raw to collectors in Malaysia at a price that is less competitive, so it was necessary to study the processing of cocoa into chocolate bars with products utilizing palm fat as a fat substitute. The purpose of this study was to determine the effect of the formulation of palm fat and cocoa fat on the physical properties of chocolate bars. The research was conducted by varying the concentration of palm fat to total fat namely 0%, 25%, 50% and 75%. The products were tested on melting point and hedonic. Based on research data it can be concluded that the treatment of palm fat concentrations to total fat by 25% produces chocolate bars with a melting point of 36.0 ° C and preferred by the panelist.